Knowledge, attitude and practice about human papilloma virus vaccination among medical students - Poonia, Hardika; Masand, Deepa Lokwani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Human papilloma virus (HPV) is one of the most common sexually transmitted infections and a major etiological factor for cervical cancer, which remains a leading cause of morbidity and mortality among women worldwide. Although safe and effective vaccines are available, awareness and vaccination coverage remain suboptimal, especially among young adults. Medical students, as future healthcare providers, play a pivotal role in promoting HPV vaccination; therefore, understanding their knowledge, attitude, and practices (KAP) is essential. Methods: A cross-sectional study was conducted among undergraduate medical students of JNU medical college, Jaipur. Data were collected using a structured, pretested questionnaire assessing participants’ knowledge about HPV infection and vaccination, their attitudes toward immunization, and their personal vaccination practices. The responses were analysed using descriptive statistics to determine awareness levels and the relationship between knowledge and vaccination behaviour. Results: The study revealed that while a majority of students had heard about HPV and its association with cervical cancer, only a smaller proportion demonstrated adequate knowledge about the recommended age, dosage schedule, and target groups for vaccination. Attitude toward HPV vaccination was generally positive, but the actual practice of vaccination among students was low. A clear gap was observed between awareness and vaccine uptake. Conclusions: Although medical students showed moderate awareness and positive attitudes toward HPV vaccination, poor vaccination practice highlights the need for targeted educational programs and inclusion of HPV-related content in the medical curriculum.